Managing hospitality organizations achieving excellence in the guest experience - Ford, Robert C. (Robert Clayton) 1945-; Sturman, Michael C. (Michael Craig) (SAGE Publications, Inc., 2020)
"Today's economy is dominated by the service sector which continues to grow at a rapid pace. Even businesses dealing primarily psychical goods are now reinventing their image and positioning themselves as service providers. Introduction to Hospitality Management: Creating Excellent Guest Experiences 2e takes students on a journey through the unique world of the hospitality industry. Each chapter focuses on a core principle of hospitality management and is packed with practical advice, examples, and cases from some of the best companies in the service sector including Walt Disney, Southwest Airlines, and The Four Seasons. Authors Michael Sturman and Robert Ford emphasize the critical importance of focusing on your guest to create that unforgettable customer experience. Whether your students will be managing a neighborhood café, a convention center, or a high-end resort hotel, they will learn invaluable skills for managing services in today's ultracompetitive environment"--